Shaping undergraduate public health education through critical race theory: a case study - Tagorda-Kama, Michelle A.; Patil, Uday; Chung-Do, Jane J.; Kehl, Lisa; Antonio, Mapuana C. K.; Nelson-Hurwitz, Denise C. (Frontiers in Public Health, 2023)
In 2020, the American Public Health Association declared structural racism a public health crisis acknowledging the long-lasting and harmful effects of prejudice, including relatively high rates of morbidity and mortality in many communities of color. Critical Race Theory (CRT) has become an essential lens to view and reconsider education’s role in perpetuating racial and ethnic discrimination. Debates over integrating CRT in higher education with the intent to acknowledge and address racial equality and justice are more present than ever, and the discussions held in public health classrooms are no different. We present a case study of CRT integration into the Bachelor of Arts in Public Health (BAPH) program at the University of Hawaiʻi at Mānoa. In line with Solorzano’s framework of CRT in education, initial goals of integrating CRT in instruction and advising included fostering discussions of race and racism, using a social justice framework to highlight opportunities to reduce health inequities, and validating the experiential knowledge of people of color. By engaging in active discussions with community leaders and participating in experiential learning throughout the program, students develop empathy and many underrepresented and marginalized students engage actively in their home communities. Specific examples of CRT integrated in the curriculum and examples of student projects that integrate a CRT lens are provided for educators and researchers.